Architectural Narrative Shapes Brain Activities Underlying Approach-Avoidance Response: A Case Study of the Stadium - Zhang, Weixia; Wei, Hongyang; Chen, Xiaowen; Hou, Yuyang; Zhang, Yujie; Huang, Qian (Frontiers in Neuroscience, 2022)
Each great architecture tells a story to make its space meaningful. What the stadium tells matters how the individual interacts with it. The potent influence of narrative in shaping our cognitive processing has been revealed and widely used. This influence, however, has been neglected by researchers in stadium operations. The present study aimed at investigating the influence of narrative on approach-avoidance responses and the corresponding neural correlates. Participants were presented with sequence of pictures expressing impressions congruent or incongruent with the general profile of the stadium, and were required to make enter or exit response towards the stadium. Results showed larger amplitudes of N400 for incongruent trials than congruent trials at the end of narrative, indicating the feasibility of continuity editing procedure for enabling stadium telling. Moreover, larger amplitudes of LPP were observed in response to stadium preceded by congruent trials than incongruent trials. This effect has a left lateral location in frontal sites. The LPP suggested that congruent narrative imparted the stadium positive affective features, and induced approaching responses, which was consistent with the behavioral results. Our findings suggested that changes in narrative were sufficient to shape the approach-avoidance responses and the underlying neural correlates. Implications for stadium management and buildings are provided.